Tears of Joy as an Emotional Expression of the Meaning of Life - Paoli, Bernardo; Giubilei, Rachele; De Gregorio, Eugenio (Frontiers in Psychology, 2022)
The article describes a research project started from a clinical experience in which dimorphic emotional expressions, together with considerations about the meaning of life, have assumed a fundamental role. On the basis of the suggestions coming from this experience we carried out a qualitative research in which we conducted 24 semi-structured interviews and a subsequent data analysis with the software MAXQDA, in order to investigate a particular dimorphic emotional expression: tears of joy. The working hypothesis is that tears of joy is not only an atypical expression due to a "super joy", or that it is only an attempt by the organism to self-regulate the excess of joyful emotion through the expression of the opposite emotion (sadness), but that it is an emotional experience in its own right - not entirely superimposable with joy - with a specific adaptive function. Through the interviews, conducted in a cross-cultural context (mainly in India and Japan), this possibility was explored: what if the adaptive function of crying for joy was to signal, to those who are experiencing it, what is the meaning of their life, the most important direction to give to their existence? The material collected provided positive support for this interpretation.